Оптимизация энергетических параметров передачи позиционных кодов сигналами с комбинированной модуляцией - Рассомахин, С. Г. (НТУ "ХПИ", 2007)
The method of improving transmission of position numbers is considered on the basis of the OFDM signals which use additional amplitude manipulation of quadrature constituents. The optimization problem of energy redistribution between bearing frequencies has been decided. The decrease possibility of relative potency of noise renewal by 10–15 dB has been received without additional power expenses.
Keywords: автоматизированные системы управления; обмен информацией; импульсно-кодовая модуляция; передача информации; частотное разделение; мультиплексирование